1996
DOI: 10.1074/jbc.271.7.3779
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mitogen-activated Protein Kinase Phosphorylation Sites on the Connexin-43 Gap Junction Protein

Abstract: We have previously demonstrated that epidermal growth factor induced a rapid, transient decrease in gap junctional communication and increase in serine phosphorylation on the connexin-43 gap junction protein in T51B rat liver epithelial cells. The kinase(s) responsible for phosphorylation and specific serine targets in connexin-43 have not been identified. There are three consensus mitogen-activated protein (MAP) kinase serine phosphorylation sequences in the carboxyl-terminal tail of connexin-43 and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
199
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(219 citation statements)
references
References 44 publications
19
199
1
Order By: Relevance
“…In addition to transcriptional regulation, activated kinases could influence the phosphorylation state of Cx proteins which in turn, would modulate GJC. Indeed, it has been reported that MAPK-dependent signal transduction pathways are capable of influencing the phosphorylation state of Cx43 (Warn-Cramer et al, 1996;Warn-Cramer and Lau, 2004) and inactivation of MAPKs with various inhibitors prevented the attenuation of GJC observed in response to pathophysiological stimuli (Cho et al, 2002;Lee et al, 2004). Similarly, our results with the p38 MAPK inhibitor SB202190 indicate that the MAPK pathway is responsible, in part, for the inhibitory effects of S. aureus on functional GJC in astrocytes.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to transcriptional regulation, activated kinases could influence the phosphorylation state of Cx proteins which in turn, would modulate GJC. Indeed, it has been reported that MAPK-dependent signal transduction pathways are capable of influencing the phosphorylation state of Cx43 (Warn-Cramer et al, 1996;Warn-Cramer and Lau, 2004) and inactivation of MAPKs with various inhibitors prevented the attenuation of GJC observed in response to pathophysiological stimuli (Cho et al, 2002;Lee et al, 2004). Similarly, our results with the p38 MAPK inhibitor SB202190 indicate that the MAPK pathway is responsible, in part, for the inhibitory effects of S. aureus on functional GJC in astrocytes.…”
Section: Discussionsupporting
confidence: 80%
“…We feel this provides direct evidence that P2 can be a heterogenous mixture of phosphoforms, some of which is Cx43 phosphorylated at S325/328/330 representing the 'classic' gap junction associated, Triton X-100 insoluble form of P2 (Musil & Goodenough, 1991), but some of which are, instead, formed by phosphorylation at S262 and associated with phosphorylation at S279/282, S262 and S368 which have been linked to decreases in gap junction communication (e.g., Doble et al, 2004;Lampe et al, 2000;Warn-Cramer et al, 1996).…”
Section: Phosphorylation On S262 Creates a Distinct P2 Isoform Of Cx43mentioning
confidence: 77%
“…However, which sites might be responsible was not determined. The sites where ERK1/2 phosphorylates Cx43 have been determined to be S255, S279 and S282 and when wild type Cx43 or S279/S282/S255A mutant Cx43 were expressed in HeLa cells, EGF treatment led to a migration shift in both wild type and mutant expressing cells, although inhibition of communication was only observed in wild type Cx43 expressing cells (Warn-Cramer et al, 1998;Warn-Cramer et al, 1996). Inhibition of ERK1/2 reversed both of these effects.…”
Section: Induced Phosphorylation Can Lead To a Distinct P2mentioning
confidence: 99%
“…Phosphorylation of Cx43 is an important regulatory mechanism for gap junctional communication. Studies in cultured neonatal rat cardiomyocytes have identified multiple sites on Cx43 for phosphorylation by several kinases (22,37,47). Schultz et al (38) reported that colocalization of PKCĪ±, p38MAPKĪ±, and p38MAPKĪ² with Cx43 during ischemia increased only in preconditioned pig hearts and preserved phosphorylation of Cx43 during ischemia.…”
Section: Introductionmentioning
confidence: 99%